Nightmares and insomnia are frequent in patients with functional neurological disorders - Schede, Corinna; Popkirov, Stoyan; Hartmann, Armin; Klein, E.; Frase, Lukas; Jöbges, Michael; Herrmann, C.; Lahmann, Claas; Spiegelhalder, Kai; Spieler, Derek; Schredl, Michael; Joos, Andreas (Journal of psychosomatic research, 2025)
Background - Functional neurological disorder (FND) is often associated with trauma and dissociation. There is insufficient data on sleep disturbances and nightmare frequency. - Methods - Patients with FND (n = 87) were compared with psychosomatic patients (PSM; mainly with affective and somatoform disorders; n = 97) and post-stroke patients (STR; n = 92). Questions focused on subjective sleep behaviour, nightmare frequency and nightmare distress. Current physical and mental health, childhood trauma and dissociative symptoms were used for ordinal regression analyses. Nightmare frequency was also compared to a representative sample of the general population. - Results - More than 70 % of FND and PSM patients reported insomnia symptoms. The restorative value of sleep was low in FND and PSM patients and was associated with physical and mental health (effect sizes d = 0.47 and d = 0.56) and dissociative symptoms (d = −0.26) across all groups, showing trends for the latter two in FND patients (d = 0.38 and d = −0.39). Thirty percent of FND and PSM patients reported nightmares at least once a week, compared to 10 % of STR patients and about 2 % in the representative sample. Across all groups, nightmare frequency was associated with current mental health (d = −0.43), dissociative symptoms (d = 0.37) and childhood trauma (d = 0.32), and in FND patients specifically with dissociative symptoms (d = 0.58). Nightmare distress was high in FND and PSM patients. - Conclusion - FND patients showed high prevalences of insomnia and nightmares, which is of clinical relevance. Associations with (daytime) mental health and dissociative symptoms underline the interplay between waking-life psychopathology, sleep and dreams, i.e. the continuity hypothesis of sleep and wakefulness.
Online verfügbar: 26. Juli 2025, Artikelversion: 2. August 2025
Gesehen am 12.11.2025